Legal Consequences of Duplicate Land Certificates in Cases of Transfer of Inheritance Rights - Satria Linanda, Ivan Rizal; Arifullah, Achmad (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
This study aims to analyze the legal consequences of the issuance of multiple land certificates in the transfer of rights due to inheritance, examine efforts to resolve disputes that arise, and describe the form of the deed of transfer of land rights due to inheritance made by the Land Deed Making Officer (PPAT) in accordance with the provisions of laws and regulations. The research method used is normative juridical with a statute approach and a case approach, and is analyzed qualitatively based on primary, secondary, and tertiary legal materials. Data are analyzed using the theory of legal certainty and the theory of legal protection as a conceptual basis. The results of the study indicate that the issuance of multiple certificates in the transfer of inheritance rights causes legal consequences in the form of defects in land administration, so that one of the certificates must be canceled to restore legal certainty for the legitimate rights holder. The National Land Agency (BPN) is responsible for making administrative corrections, while disputes that arise can be resolved through litigation (General Court or PTUN) or non-litigation (deliberation, mediation, or arbitration). From a formal perspective, the creation of a deed of transfer of rights due to inheritance by a PPAT functions as authentic evidence and the basis for recording changes in rights at the Land Office as regulated in Articles 37 and 42 of Government Regulation Number 24 of 1997 concerning Land Registration and Regulation of the Minister of ATR/BPN Number 3 of 1997.